2021
DOI: 10.3390/nano11040943
|View full text |Cite
|
Sign up to set email alerts
|

Blue Electroluminescence in SRO-HFCVD Films

Abstract: In this work, electroluminescence in Metal-Insulator-Semiconductors (MIS) and Metal-Insulator-Metal (MIM)-type structures was studied. These structures were fabricated with single- and double-layer silicon-rich-oxide (SRO) films by means of Hot Filament Chemical Vapor Deposition (HFCVD), gold and indium tin oxide (ITO) were used on silicon and quartz substrates as a back and front contact, respectively. The thickness, refractive indices, and excess silicon of the SRO films were analyzed. The behavior of the MI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 50 publications
(105 reference statements)
0
1
0
Order By: Relevance
“…A material of great technological interest in silicon optoelectronic research is silicon-rich oxide (SRO), which has been reported on multiple occasions as a material with nanostructures intrinsically formed within it. An outstanding characteristic of the SRO is that it facilitates the formation of silicon nanocrystals (Si-ncs) embedded in a SiO 2 matrix [ 7 ], where electron quantum confinement is generated due to low-dimensional effects, leading to an efficient light emission [ 8 ]. Apart from the effects related to quantum confinement in nanostructures, it has been reported the presence of intrinsic defects in the SRO films that favor the radiative emission [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…A material of great technological interest in silicon optoelectronic research is silicon-rich oxide (SRO), which has been reported on multiple occasions as a material with nanostructures intrinsically formed within it. An outstanding characteristic of the SRO is that it facilitates the formation of silicon nanocrystals (Si-ncs) embedded in a SiO 2 matrix [ 7 ], where electron quantum confinement is generated due to low-dimensional effects, leading to an efficient light emission [ 8 ]. Apart from the effects related to quantum confinement in nanostructures, it has been reported the presence of intrinsic defects in the SRO films that favor the radiative emission [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%